Partial hominin tibia (StW 396) from Sterkfontein, South Africa - Zipfel, Bernhard; Berger, Lee R. (Bernard Price Institute for Palaeontological Research, University of the Witwatersrand, 2009)
Comparison of a proximal hominin tibial fragment, StW 396 from Sterkfontein Member 4, South Africa, with the StW 514a tibia, also from Member 4 and attributed to Australopithecus africanus, indicates a degree of morphological variability that may represent the extremes of intraspecific variability or even exceed what one would expect from intraspecific variation alone. The morphology of StW 396 is human-like which suggests adaptations towards stability at the knee, whilst that of StW 514a is interpreted as being more mobile and ape-like (Berger & Tobias 1996). Four features separate the two morphological patterns. In StW 514a the attachment area of m. semimembranosus is strongly localized, whereas in StW 396 the posteromedial border is notched near the base of the lateral intercondylar tubercle; thirdly, the lateral tibial condyle of StW 514a is supero-inferiorly thin, whereas in StW 396 the lateral condyle is supero-inferiorly thickened and the contrast between the condyle and the shaft is less pronounced; lastly the articular surface of the medial condyle of StW 396 is anteroposteriorly broad and highly concave as opposed to the narrower, flatter surface of StW 514a. The degree of variability of the two specimens possibly suggests differing functional adaptations and may thus support an hypothesis suggesting that two hominin species may be represented within Sterkfontein Member 4.
Keywords: hominin; tibia; Sterkfontein; Australopithecus africanus